2010
DOI: 10.1084/jem.20090516
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid DAP12-associating lectin (MDL)-1 regulates synovial inflammation and bone erosion associated with autoimmune arthritis

Abstract: DNAX adaptor protein 12 (DAP12) is a trans-membrane adaptor molecule that transduces activating signals in NK and myeloid cells. Absence of functional Dap12 results in osteoclast defects and bone abnormalities. Because DAP12 has no extracelluar binding domains, it must pair with cell surface receptors for signal transduction. There are at least 15 known DAP12-associating cell surface receptors with distinct temporal and cell type–specific expression patterns. Our aim was to determine which receptors may be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
98
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 24 publications
(36 reference statements)
14
98
0
Order By: Relevance
“…It is not clear whether BCR or FcR is involved because B cell and humoral autoimmunity have not been shown to contribute to AIA. Other possible receptors include CSF1R and myeloid DAP12-associating lectin-1, both of which depend on ITAM-containing DAP12 for signaling, and are implicated in immune arthritis in rodents (Huang et al, 2009;Joyce-Shaikh et al, 2010). Although the exact mechanism remains to be defined, our data suggest that Btk inhibitors may also produce efficacy in autoimmune conditions in which T cell and innate immune responses dominate.…”
Section: Btk Inhibitors For Rheumatoid Arthritis 99mentioning
confidence: 83%
See 1 more Smart Citation
“…It is not clear whether BCR or FcR is involved because B cell and humoral autoimmunity have not been shown to contribute to AIA. Other possible receptors include CSF1R and myeloid DAP12-associating lectin-1, both of which depend on ITAM-containing DAP12 for signaling, and are implicated in immune arthritis in rodents (Huang et al, 2009;Joyce-Shaikh et al, 2010). Although the exact mechanism remains to be defined, our data suggest that Btk inhibitors may also produce efficacy in autoimmune conditions in which T cell and innate immune responses dominate.…”
Section: Btk Inhibitors For Rheumatoid Arthritis 99mentioning
confidence: 83%
“…DAP12 functions as an adaptor protein for multiple receptors, including macrophage colony-stimulating factor 1 receptor (CSF1R) and myeloid DAP12-associating lectin-1 receptor. Both receptors have been implicated in the development of immune arthritis (Huang et al, 2009;Joyce-Shaikh et al, 2010). Also importantly, CSF1R, along with FcR gamma chain, provides a secondary, but indispensable, signal for RANKL to promote osteoclast differentiation and, subsequently, bone resorption (Koga et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We were interested to see whether these receptors are present on OCPs and found that receptors providing cosignaling through DAP12 and FcRγ were present on the OCP cell surface. Triggering receptor expressed on monocytes (TREM-2) and myeloid DAP12-associating lectin (MDL-1, also known as CLEC-5A), both DAP12-associated receptors, have been shown to costimulate osteoclast differentiation (27)(28)(29), and MDL-1 was recently implicated in osteoclast differentiation and inflammatory bone loss (30). TREM-2 levels on OCPs were quite low, while MDL-1 expression was high on OCPs ( Figure 4D).…”
Section: Skg Arthritis Results In Osteopenia and Erosive Bone Lesionsmentioning
confidence: 99%
“…These samples were originally analyzed for CD4 + and dendritic cell apoptosis (52). The samples were then restained with a novel antibody that is expressed on activated myeloid cells: myeloid DAP12-associating lectin-1 (MDL-1), a cell-surface receptor which has been shown to regulate myeloid cell-associated inflammatory responses (53,54 from bone marrow and the peripheral blood (54). As shown in Figure 6, the pattern of MDL1 expression on human spleens increased dramatically with trauma and sepsis.…”
Section: Mdscs In Trauma and Sepsis: Pathophysiologic Or Beneficial?mentioning
confidence: 99%